Le contrôle juridique des précipitations acides - Grandbois, Maryse (Les Cahiers de droit, 1985)
Acid rain — which is a result of chemical alteration of sulfur and nitrogen oxydes when combined in the atmosphere with moisture — each year causes damages beyond repair to the environment. Because of the long-range transportation of pollutants and the local sensitivity of soils, Eastern Canada is particularly affected. The Province of Quebec is one prime target and it receives downwind air pollutants from the United States and Ontario. This article deals with the law as it relates to acid rain and studies recent developments at local, national and international levels. It analyses laws, regulations and by-laws under which governments regulate and control the precursor pollutants of acid rain. Until now government has not satisfactorily addressed the problem of acid rain so as to propose legal solutions. This is partly due to long-range transportation of pollutants which raises the question to an international level, making the issue of a negotiation on the subject between Canada and United States crucial.